Phase Unwrapping In SAR Interferometry - Tay, Lea Tien (2001)
Various phase unwrapping algorithms have been developed for extraction of topographic digital terrain model (DTM) and displacement detection in SAR Interferometry since 1988. However, problems such as accuracy and speed of phase unwrapping process still remain a challenge for SAR Interferometry applications. In this thesis, both path following and least square methods for phase unwrapping are analysed. Path following method includes branch-cut, guality-guided, mask-cut and minimum discontinuity methods while least square method covers both weighted least square and unweighted least square method. Quality-guided and mask-cut methods need quality information, whereas minimum discontinuity and least square methods can be implemented either with or without quality information. Quality information applied in this project are correlation map, phase derivative variance map and maximum phase gradient map. The disadvantages associated with weighted minimum discontinuity method and weighted least square method using quality maps are low accuracy and long execution time. Therefore in this project, the use of mask maps in weighted minimum discountinuity method and weighted least square method is studied to subtitute quality maps. This will increase the accuracy of the unwrapped results and reduce the execution time. In addition, we study the possibilities of mask maps to replace quality maps in mask-cut method. We also introduce residue-based quality maps for quality-guided method and residue-based mask maps for mask-cut method, weighted minimum discontinuity method and weighted least square method. The motivition of studying residue-based quality maps and residue-based mask maps is that most of the errors in the unwrapped results propagate from the residue pixels, i.e. phase inconsistencies. Residue-based quality maps and residue-based mask maps deal with the residues directly by masking out them in the maps and this will reduce error propagation. The implementations of residue-based quality maps in quality -guided method, residue-based mask maps and conventional mask maps in mask-cut method, weighted minimum discontinuity method and weighted least square method are applied on two simulated SAR images, I.e. Long's Peak image and Isolation Peak image. The unwrapped solutions are analysed based on the their accuracy percentages, average execution time and memory requirements. The evaluations and comparisons between unwrapped solution of our proposed method and those of existing method are carried out in this project. The application of mask maps in weighted minimum discontinuity method and weighted least square method give satisfactory results with higher accuracy and shorter execution time as compared to those using quality maps. In general, residue-based quality maps and residue-based mask maps are found to be more suitable in phase unwrapping algorithms than quality maps and mask maps respectively, because they mask out all residue pixels and thus the possibilities of errors propagating from residue pixels to other pixels are reduced significantly.